Propagation of Magnolia grandiflora Linn. By Stem Cuttings - Chandra, J. P. (Indian Forester, 1978)
Results of rooting of Magnolia grandiflora stem cutting are reported. In 92 days time under controlled temperature aad humidity, 32 per cent cuttings were able to produce roots, wilen cuttings were three season old, without any aid of root promoting hormone.